(untitled) (Medico Legal Update, 2024)
Tuberculosis is caused by Mycobacterium tuberculosis. If the treatment is inadequate or if host defenses are impaired, the apical lesion in primary tuberculosis expands into adjacent lung tissues and may spread via airways, lymphatic channels, or the vascular system. It may also circulate back to the lung and cause miliary pulmonary disease. Systemic miliary tuberculosis occurs when bacteria disseminate through the systemic arterial system to involve any organ. In the present study, we discuss five such cases of systemic miliary tuberculosis wherein the deceased succumbed to the illness.